Alasan konsumen dalam membeli dan mengonsumsi madu sebagai suplemen kesehatan - Wildiana, Resha Ayu; Lestari, Lily Arsanti; Supriyati, Supriyati (Jurnal Gizi Klinik Indonesia, 2023)
Reason for consumers to buy and consume honey as a health supplementBackground: During the COVID-19 pandemic, people believed honey was a supplement to increase body endurance. Research on consumer perceptions regarding specific health benefits has never been done. The market's production and demand for honey have not balanced, giving rise to the potential for selling fraudulent honey. It is necessary to identify the public perception regarding the health benefits of honey using one of the determinants of the theory of planned behavior and consumer knowledge regarding labels on honey products. Objective: This research was conducted to determine the factors related to consumer behavior in buying and consuming honey as a health supplement. Methods: Quantitative research using a cross-sectional survey design. Online data collection was done by distributing questionnaire links through social media in October-November 2021 in various regions of Indonesia. A total of 426 research subjects were selected using the accidental sampling technique. The data were analyzed using the Spearman correlation test. Results: Consumer knowledge about honey product labels is categorized as sufficient (48.13%) and less (44.12%). Gender and education were significantly related to the purchase of honey (p=0.0308; p=0.0101), and gender was associated with consumption behavior (p=0.0086). Perception of overall and specific health benefits (improves immunity, diabetes, cancer, heart, cough, and asthma, accelerates healing after illness, reduces the frequency of diarrhea, lower blood pressure, lower levels of fat and cholesterol in the body) were significantly related to the behavior of buying and consuming honey (p=0.0001). Knowledge is significantly related to honey consumption behavior (p=0.0363). Conclusion: Honey buying and consumption behavior in Indonesia is related to consumer perceptions of overall and specific health benefits. It is necessary to review honey labels currently on the market and increase consumer knowledge about honey product labels.